Gustavo, the shy ghost - Drago, Flavia Z. (2020)
A shy ghost pursues his secret love for playing the violin while trying to bond with monster friends who cannot see him
Ages 3-7.
Accelerated Reader AR
Lexile
F&P
Keywords: Ghost stories; Bashfulness -- Juvenile fiction; All Souls' Day -- Juvenile fiction; Violin -- Performance -- Juvenile fiction; Emotions -- Juvenile fiction; Friendship -- Juvenile fiction; Ghost stories; Picture books; Paranormal fiction; Histoires de fantômes.; Livres d'images.